Tierra prometida – Spain as Jewish past and future - Katz, Marco (My University, 2016)
“[H]e told me,” writes Benito Pérez Galdós, “that the Jews either had no country or had two, their current home or their traditional one, Spain”1 (224). [Vocal rendition of “Hevenu Shalom Aleichem / La paz esté con vosotros” in Hebrew and Spanish.] “Hevenu Shalom Aleichem,” a melody I recall from as long as I have memories. “Hevenu shalom Aleichem. Hevenu shalom Aleichem. Hevenu shalom Aleichem. Hevenu shalom, shalom, shalom Aleichem.” I also remember it this way: “La paz esté con vosotros. La paz esté con vosotros. La paz esté con vosotros y con vosotros siempre, siempre esté en paz.” A cosmopolitan song for wandering people. The apogee of this cosmopolitan took place under Islamic rule of a Peninsula that created the conditions for what we now call modern Jewish culture. Today, I consider how cosmopolitanism led Jews to become Spanish, then survive and sometimes flourish as Spaniards in America, and finally infect Spanish Americans with cosmopolitanism.
Presented on March 18, 2016 at the American Comparative Literature Association Annual Meeting held at Harvard University in Cambridge, Massachusetts.
Keywords: Spanish Jews; cosmopolitanism